Efektivitas Peran Mediator dalam Konflik Hukum Perdata - Ma'ruf, Rahma (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Mediation is a process where an individual serves as a mediator to facilitate communication between the parties in dispute, allowing their differing perspectives on the issue to be understood and potentially resolved. Mediation that results in a peace agreement will represent a full resolution since the outcome does not rely on a win or lose approach. Reaching a settlement via the mediation process offers numerous advantages for the parties involved; the time involved will lower costs, making it more economical. From an emotional standpoint, mediation settlements can bring relief to the parties, as the terms of agreement are established by the parties themselves based on their preferences. Mediation has essentially been around for a long time, as the approach to resolving conflicts in society typically employs the concept of mediation. Mediation is an action taken by an individual to settle a conflict between two or more parties through negotiation in order to achieve peace. When an unbiased and neutral external entity collaborates with the conflicting parties to assist them in achieving a resolution. The assumption is that an external party can alter the intensity and social dynamics of the conflict relationship by impacting the beliefs and actions of the involved parties, by offering knowledge and information, or by employing the negotiation process. In settling conflicts via mediation, it is anticipated that the involved parties can typically come to a mutual agreement, ensuring that the advantages of mediation are significantly experienced. Essentially, Mediation allows the parties to engage directly and informally in settling their conflicts. Mediation reports are categorized as successful, unsuccessful, and non-implementable mediation.